Development of an Inventory of Dental Harms: Methods and Rationale. Issue 6 (30th September 2022) - Kalenderian, Elsbeth; Lee, Joo Hyun; Obadan-Udoh, Enihomo M.; Yansane, Alfa; White, Joel M.; Walji, Muhammad F.
Abstract : Objectives: While adverse events (AEs) are all too prevalent, their underlying causes are difficult to assess because they are often multifactorial. Standardizing the language of dental AEs is an important first step toward increasing patient safety for the dental patient. Methods: We followed a multimodal approach building a dental AE inventory, which included a literature review; review of the MAUDE database; a cross-sectional, self-administered patient survey; focus groups; interviews with providers and domain experts; and chart reviews. Results: One hundred eight unique allergy/toxicity/foreign body response, 70 aspiration/ingestion of foreign body, 70 infection, 52 wrong site/wrong patient/wrong procedure, 23 bleeding, 48 pain, 149 hard tissue injury, 127 soft tissue injury, 91 nerve injury, 171 other systemic complication, and 177 other orofacial complication were identified. Subtype AEs within the categories revealed that allergic reaction, aspiration, pain, and wrong procedure were the most common AEs identified among known (i.e., chart reviews) and hypothetical (i.e., interviews) sources. Conclusions: Using a multimodal approach, a broad list of dental AEs was developed, in which the AEs were classed into 12 categories. Hard tissue injury was noted frequently during interviews and in actuality. Pain was the unexpected AE that was consistently identified with every modality used. Practical Implications: Most AEs result in temporary harm with hard tissue injury being a common AE identified through interviews and in actuality through chart reviews. Acknowledging that AEs happen is an important step toward mitigating them and assuring quality of care for our patients.